Incidence, risk factors and outcome of multi-drug resistant Acinetobacter baumannii nosocomial infections during an outbreak in a burn unit - Anne-Lise Munier; Lucie Biard; Matthieu Legrand; Clotilde Rousseau; Matthieu Lafaurie; Jean-Luc Donay; Rémi Flicoteaux; Alexandre Mebazaa; Maurice Mimoun; Jean-Michel Molina (International Journal of Infectious Diseases, 2019)
Background: Multidrug-Resistant Acinetobacter baumannii (MR-AB) can cause outbreaks in burn units. We aimed to study the incidence, risk factors and outcome of MR-AB infections in a burn unit (BU). Methods: A prospective study was conducted from April to November, 2014 during an outbreak in a BU in Paris. Weekly surveillance cultures were performed to determine MR-AB colonization. MR-AB nosocomial infections, discharge or death without MR-AB infection were considered as competing events. To identify risk factors for MR-AB infection, baseline characteristics and time-dependent variables were investigated in univariate analyses using Cox models. Results: Eighty-six patients admissions were analyzed during the study period. Among them, 15 (17%) acquired MR-AB nosocomial infection. Median time to infection was 22 days (interquartile range: 10–26 days). Cumulative incidence of MR-AB infections was 15% at 28 days (95% CI = 8–24). Risk factors for MR-AB infection in univariate analysis were SAPS II (Hazard Ratio (HR):1.08; 95% CI:1.05–1.12; P < 0.0001) and ABSI (Abbreviated Burn Severity Index) scores (HR:1.32; 95% CI:1.12–1.56; P = 0.001), MR-AB colonization (HR:10.2; 95%CI:2.05–50.3; P = 0.004), invasive procedures (ventilation, arterial and/or venous catheter) (P = 0.0001) and ≥2 skin grafts (HR:10.2; 95% CI:1.76–59.6; P = 0.010). MR-AB infection was associated with an increased risk of death (HR: 7.11; 95%CI: 1.52–33.2; P = 0.013) and longer hospital stay with a median estimated increase of 10 days (IQR: 6; 14). Conclusions: Incidence of MR-AB nosocomial infection was high during this outbreak, and was associated with prolonged hospitalization and increased risk of death. High patient severity scores, prior MR-AB colonization, invasive procedures and repeated skin grafts were associated with an increased risk of nosocomial infection. Keywords: Acinetobacter baumannii, Antibiotic resistance, Infection, Risk factors, Burns